Pengaruh Kompetensi, Profesionalisme Dan Etika Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik di Kota Batam - Erni Yanti Natalia (LPPM Universitas Putera Batam, 2018)
This study aims to determine the influence of competence, professionalism, and auditor ethics on audit quality at Public Accounting Firm in Batam City. The population in this study is the auditor who works at Public Accounting Firm in Batam City. The primary data retrieval method used was questionnaire method which was distributed to 50 respondents. Sampling technique using saturated samples. Data analysis method used is multiple linear regression analysis. The results of this study indicate that the competence variables have a significant effect on audit quality with significant value 0.000 < 0.05, while the variable professionalism but insignificant effect on the value of 0.267 > 0.05 and ethical effect but not significant with a value of 0.394 > 0.05 on Quality audit. Simultaneously competence, professionalism and auditor ethics have positive and significant influence to audit quality.